Psychoanalysis, COVID, and mass trauma the trauma of reality - Bakó, Tihamér 1955-; Zana, Katalin; Robinson, Richard (Abingdon, Oxon Routledge, 2023)
"Constructed as a psychoanalytic diary, the authors of this book reflect on clinical observations from their work with patients during the COVID-19 pandemic, tracking these singular experiences to arrive at broader understanding of the psychological characteristics of collective trauma. Based on the theoretical framework of their previous book, which focuses on the transgenerational, psychological effects of large-scale social-historical traumas and introduced new concepts such as the 'Transgenerational Atmosphere', the authors here explore the trauma itself, especially those deep traumas which affect a large group of people or even the whole of humanity, including pandemics, natural disasters, terrorism and war. In this volume, the authors progress toward the potential immediate and long-term psychological effects of such trauma, including the possibility of the activation of unprocessed transgenerational traumatic experiences, but also the potential for growth. Rich in clinical material and methodological suggestions, this book will appeal to mental health professionals, including psychiatrists, psychologists, psychoanalysts, and social workers, in addition to professors in other academic disciplines, such as sociology, history, philosophy and anthropology"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Generational trauma; COVID-19 (Disease) -- Psychological aspects; COVID-19 Pandemic, 2020-2023 -- Psychological aspects